Aplicación de recursos de armonía negativa dentro de la composición de cuatro piezas musicales - Escudero Mogrovejo, Alexis Ariel (2024)
The artistic product contributes to the compositional development through the creation of a repertoire of four musical works, in which the resource of negative harmony is incorporated in different genres of popular music such as rock, folk, and jazz, in a line of fusion. The strategies used in the compositional process were selected from artistic and theoretical references, as well as from personal conceptions about this resource based on experience. The artistic product was made in three phases: the first consisted of the composition of the pieces, as well as their writing and analysis in lead-sheet format; the second consisted of the recording, mixing and mastering of the phonograms; and, as a last phase, the results were socialized. The artistic proposal, within the compositional field, evidences the versatility of the negative harmony resource, exploring its symmetry perspective within functional tonal music, and intends, at the same time, to motivate other authors to implement it in their works. Keywords: Composition, popular music, negative harmony, tonal polarity.